Pengaruh Perilaku Asertif Terhadap Stress Kerja pada Karyawan PT. Indoturbine Jakarta - Suhartini Suhartini; Oryza Sativa Reswari (Jurnal Aplikasi Bisnis, 2017)
The research aims to reveal: (1) Effect of partial and simultaneous behavior of verbal and non verbal assertive response to stress in of employees of PT. Indoturbine Jakarta, (2) Determine which variable is more influential on assertive behavior to the stress ofwork at the employees of PT. Indotribune, Jakarta.Census method was employed in this study while questionnaires and literature study were chosen in gathering data. The analysis includes descriptive analysis (respondent characteristics and assessment of each variable) and statistical analysis (F test and t test).The results showed that: (1) there is a simultaneous effect, positive and significant correlation between Asseitive Behavior (Verbal Ability and Non-Verbal Ability) of the Employee Stress PT. Indoturbine, Jakarta, (2) there is a partial influence of variable Assertive Verbal Ability ofthe Stress ofwork and there is a partial variable influence Assertive Non-Verbal Ability ofthe work stress, and (3) Verbal Ability Assertive behavior isthe most influential variable ofthe Working Stress employees of PT.Indoturbine, Jakarta.